2000
DOI: 10.1136/vr.147.7.179
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards badger culling to control bovine tuberculosis in cattle

Abstract: In 1999, a questionnaire survey was conducted to evaluate public preferences towards badger culling to control bovine tuberculosis in cattle. Three alternative treatments were considered: (1) widespread culling, (2) the current experimental trials, and (3) no culling. One hundred residents from Glastonbury and York were interviewed in person and asked to give preference ratings to each of the three treatments. The single most preferred treatment was no culling, and the least preferred was the widespread cull. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…1999) representative. The extent to which the respondents are representative should be quantified, for example by resurveying the non‐respondents (Heydon & Reynolds 2000) or by statistical comparison of the respondents with the intended sample population (White & Whiting 2000; as undertaken here).…”
Section: Discussionmentioning
confidence: 99%
“…1999) representative. The extent to which the respondents are representative should be quantified, for example by resurveying the non‐respondents (Heydon & Reynolds 2000) or by statistical comparison of the respondents with the intended sample population (White & Whiting 2000; as undertaken here).…”
Section: Discussionmentioning
confidence: 99%
“…These trade‐offs are then used to derive preferences or valuations for the environmental variables indirectly. This technique has been used recently to inform decision‐making for wildlife management policy in Britain (Cox, 1999; Cox et al , 1999; White & Whiting 2000), although its wider applicability for valuation is dependent on the existence of meaningful environment–monetary trade‐offs for the construction of the alternative policy scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that M. bovis infections in badgers and cattle are associated in space (Woodroffe et al, 2005c;Jenkins et al, 2007), and experimental reduction of badger density by culling over large ($100 km 2 ) tracts of land has been found to lower the incidence of cattle TB inside culled areas (Griffin et al, 2005;Donnelly et al, 2006). However, such widespread badger culling is labor-intensive, costly, and unpopular with the general public (Dunnet et al, 1986;White and Whiting, 2000;Woodroffe et al, 2008). For these reasons, past TB control policies restricted badger culling to localized areas centered on farms that had recently experienced TB incidents in cattle (termed ''herd breakdowns'').…”
Section: Introductionmentioning
confidence: 99%